Cooperative treatment and resource utilization process for CO2 in industrial solid waste and tail gas
Through the static reaction method of polyacids and catalytic accelerator, the alumina and iron oxide in industrial solid waste are converted into soluble salts. Combined with ammonia replacement and activated carbon catalysts, the problems of low comprehensive utilization rate of industrial solid waste and serious carbon dioxide emissions are solved, and efficient resource utilization and carbon dioxide recovery are achieved.
Patent Information
- Application Number
- CN202510443944.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-04-09
AI Technical Summary
In the prior art, the comprehensive utilization rate of industrial solid waste such as fly ash, gasified slag and coal gangue is low, and carbon dioxide emissions are severe, and effective coordinated governance and resource utilization methods are lacking.
The alumina and iron oxide in the gasified slag is converted into soluble salts by static reaction, and the ammonia displacement method is used to separate iron hydroxide and aluminum hydroxide. activate carbon is used as a catalyst to absorb carbon dioxide to produce silica acid and sodium carbonate, thereby achieving efficient extraction and recovery of resources.
It has achieved efficient resource utilization of gasified slag, fly ash and coal gangue, and generated high-value-added products such as alumina, sodium silicate and activated carbon, reducing carbon dioxide emissions and reducing environmental pollution.
Smart Images

Figure CN120243615A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental protection technologies, and in particular to a process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas. Background Art
[0002] The treatment and utilization of bulk industrial solid waste include the comprehensive utilization of bulk waste such as fly ash generated from coal combustion, gasification slag generated from deep processing of coal chemical industry, and coal gangue generated from coal mining. In China, the annual output of fly ash from coal-fired power plants exceeds 800 million tons, and the cumulative storage capacity is greater than 3 billion tons. The annual output of gasification slag from deep processing of coal chemical industry is greater than 70 million tons, and the cumulative storage capacity is greater than 300 million tons. The annual output of coal gangue, an associated product of coal mining, is greater than 800 million tons, and the cumulative stockpile exceeds 5 billion tons. The large-scale storage of these wastes not only occupies land resources, but also causes varying degrees of pollution to the atmospheric environment, soil and groundwater in the absence of effective management. At present, conventional treatment measures mostly adopt the method of separate treatment for each monomer. Among them, the main treatment approach for gasification slag is to extract residual carbon, and the waste slag after extracting residual carbon is used in various fields such as building materials, road engineering, backfilling engineering, and agriculture, with a utilization rate of less than 50%. Due to the large amount of fly ash generated, part of it is used in the building materials industry, and most of it is landfilled. Except for a small part of coal gangue used for waste heat utilization by co-firing, most of it is backfilled into mines or landfilled underground. In the building materials industry, fly ash and gasification slag are mainly used in the production of new wall materials such as cement, commercial concrete, fly ash bricks, gasification slag bricks, and aerated concrete products. In road construction projects, the main utilization forms of fly ash and gasification slag are as roadbeds and as admixtures for road surface concrete. The utilization amount of fly ash and gasification slag through the above-mentioned channels is small, the product quality is uncertain, and the added value of comprehensive utilization is low. In agriculture, gasification slag is mainly used for soil improvement and nutrient fertilizers. Due to the complex composition of gasification slag, in addition to containing trace amounts of available nutrient elements, there are also a large number of harmful metal elements and heavy metal elements. When plants absorb beneficial nutrient components, they will also absorb harmful metal elements. On the one hand, these harmful metal elements will remain in the plants and fruits, which is harmful to human health. On the other hand, they will seep into the ground and pollute the soil and groundwater. Therefore, these components pose great uncertainties to human health and soil safety, and the secondary pollution is serious. Therefore, high-value comprehensive utilization technologies for bulk industrial wastes such as fly ash, gasification slag, and coal gangue still need to be developed and expanded.
[0003] Carbon dioxide is an inevitable product of industrial development. In recent years, due to the accelerating pace of global industrialization, carbon dioxide emissions have become a major hidden danger threatening the survival and development of humanity. The warming of the climate, the decline in ecological carrying capacity, the imbalance of the atmospheric circulation, and the sharp increase in extreme meteorological events all indicate that the accumulation of carbon dioxide in the atmosphere has reached a critical point. The emission of carbon dioxide has reached a position that endangers human survival. Therefore, the reduction, capture, and recycling of carbon dioxide in industrial production are the key factors and important thresholds restricting future industrial development. The technologies for carbon dioxide capture, recycling, and utilization will become the most concerned topics globally in the sustainable development of industrialization. Summary of the Invention
[0004] The purpose of the present invention is to provide a process for the collaborative treatment and resource utilization of CO2 in industrial solid waste and tail gas to solve the above technical problems.
[0005] To achieve the above invention purpose, the present invention provides the following technical solutions:
[0006] The present invention provides a process for the collaborative treatment and resource utilization of CO2 in industrial solid waste and tail gas, including the following steps:
[0007] Step 1): The gasification slag, hydrochloric acid solution, sulfuric acid solution, and nitric acid solution are mixed in sequence to obtain slurry 1, and then the catalytic promoter and slurry 1 are mixed to obtain slurry 2. Then, stacking and neutralization, washing and dissolution, and pressure filtration separation are carried out in sequence to obtain slag material 1 and mixed solution 1;
[0008] The mixed solution 1 is a mixed solution containing aluminate and ferrate;
[0009] Step 2): The ammonia replacement method is used to first replace iron hydroxide and heavy metal hydroxides in the mixed solution 1, raise the pH value to replace aluminum hydroxide precipitate and polyacid ammonium solution, and the aluminum hydroxide precipitate is heat-treated to make alumina finished product, or neutralized with hydrochloric acid to make aluminum chloride finished product;
[0010] Step 3): The obtained polyacid ammonium solution is pyrolyzed to obtain ammonia gas and polyacid residual liquid. The ammonia gas is recycled to the ammonia replacement method in Step 2), and the polyacid residual liquid is recycled to the preparation of slurry 1;
[0011] Step 4): The obtained slag material 1 is subjected to the first alkali dissolution, and then water dissolution and pressure filtration separation are carried out in sequence to obtain mixed solution 2 and slag material 2;
[0012] The mixed solution 2 is a mixed solution containing sodium silicate and sodium tetrahydroxyaluminate;
[0013] Step 5): The obtained slag 2 is subjected to a second alkali dissolution, followed by dissolution in clear water and pressure filtration separation to obtain a mixed solution 3 and slag 3. The slag 3 is dried and activated to make activated carbon, which is then mixed with fly ash and / or coal gangue fine powder as a catalyst and reused in Step 1).
[0014] The mixed solution 3 is a mixed solution containing sodium silicate.
[0015] Step 6): The mixed solution 2 reacts by absorbing carbon dioxide produced in the process tail gas, and is filtered to obtain solid 1 and sodium carbonate solution.
[0016] Solid 1 is a mixture of silicic acid and aluminum hydroxide.
[0017] Step 7): The mixed solution 3 reacts by absorbing carbon dioxide produced in the process tail gas, and is filtered to obtain silicic acid and sodium carbonate solution.
[0018] Step 8): The sodium carbonate solutions obtained in Step 6) and Step 7) are combined and calcium hydroxide is added for causticization reaction to obtain sodium hydroxide solution and calcium carbonate. The sodium hydroxide solution can be recycled, and the calcium carbonate is dried to make a finished product.
[0019] Step 9): The silicic acid obtained in Step 7) is hydrothermally synthesized and then dried to make a silica product. The mixture of silicic acid and aluminum hydroxide obtained in Step 6) is mixed with the heavy metal hydroxide obtained in Step 2) to prepare a high-aluminum molecular sieve.
[0020] In Step 1), the main components of the gasification slag include alumina and iron oxide.
[0021] According to the component contents of alumina and iron oxide in the gasification slag, the dosage of the acid is prepared by calculating the percentage of the relative molecular masses of various acids consumed in converting alumina and iron oxide according to the chemical reaction formula.
[0022] The mass concentration of the hydrochloric acid solution is 35 - 37%, the mass concentration of the sulfuric acid solution is 50 - 98%, the mass concentration of the nitric acid solution is 50 - 98%, and the ratio of the hydrochloric acid solution, sulfuric acid solution and nitric acid solution is 5 - 15%: 5 - 15%: 70 - 90%.
[0023] The catalytic effect of the surface activity of the residual carbon refers to that the abundant active sites on the surface of the residual carbon have the ability to accept electrons and donate electrons, and can generate electrochemical reactions.
[0024] Further, in step 1), the catalytic promoter includes hydrogen peroxide and / or an oxygen-containing acid solution of chlorine. The volume concentration of the hydrogen peroxide solution is 27.5 - 40%, the concentration of the oxygen-containing acid solution of chlorine is 25 - 30%, and the oxygen-containing acid of chlorine in the oxygen-containing acid solution of chlorine includes one or more of HClO4, HClO3, HClO2, and HClO;
[0025] The total amount of the hydrogen peroxide solution and the oxygen-containing acid solution of chlorine accounts for 5 - 10% of the sum of the masses of the hydrochloric acid solution, sulfuric acid solution, and nitric acid solution.
[0026] Further, in step 1), the temperature of the heap retting and neutralization is 50 - 80 °C, and the time of the heap retting and neutralization is 8 - 12 h;
[0027] The washing and dissolving is washing and dissolving with clear water, and the water-to-material ratio is 3 - 5:1.
[0028] Further, in step 2), the ammonia replacement method includes adding ammonia water or introducing ammonia gas.
[0029] Further, in step 2), the aluminum hydroxide precipitate is made into alumina finished product through heat treatment. When the heat treatment temperature is 140 - 150 °C, γ-alumina is obtained;
[0030] When the heat treatment temperature is 900 °C - 1200 °C, α-alumina is obtained;
[0031] The concentration of the hydrochloric acid solution in the hydrochloric acid neutralization reaction is ≥25 wt%;
[0032] The hydrochloric acid neutralization reaction makes aluminum chloride crystals rapidly precipitate out from the aluminum chloride solution through the common ion effect. The crystals are aluminum chloride hexahydrate, and the mass concentration of the added hydrochloric acid is greater than 30%.
[0033] Further, in step 4), the reagent used for the first alkali dissolution is sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is 20 - 42%.
[0034] Further, in step 5), the reagent used for the second alkali dissolution is sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is 30 - 42%.
[0035] Further, in step 5), the volume ratio of the fly ash and / or coal gangue micro-powder to the activated carbon is 1:0.2 - 0.5.
[0036] The beneficial effects of the present invention:
[0037] The co-treatment and resource utilization process of industrial waste gasification slag, fly ash, coal gangue and carbon dioxide in waste gas realized by the present invention not only realizes the resource utilization of legal aluminum extraction, silicon extraction and decarbonization of gasification slag, fly ash and coal gangue, but also produces a synergistic effect in the process of resource utilization, turning harmful pollutants into beneficial substances and generating huge added value. The following objectives can be achieved accordingly:
[0038] 1). Through the aqua regia effect of polybasic acid in chemical reactions, the reaction activity of reactants is improved;
[0039] 2). Transform the residual carbon in the gasification slag into a catalyst that can promote aluminum extraction and silicon extraction from fly ash and coal gangue, provide an electrochemical reaction carrier for the aluminum extraction and silicon extraction reaction, and enhance the efficacy of chemical reactions;
[0040] 3). Utilize H2O2, HClO4, HClO3, HClO2, HClO as catalytic promoters, enhance the reaction activity of oxidants while assisting the catalyst to generate electrochemical effects, and improve the oxidation performance of oxidants;
[0041] 4). Absorb carbon dioxide through the generated sodium silicate, recover carbon dioxide in the process while obtaining a cheap ion exchange medium, and enable the overall process to achieve a synergistic effect;
[0042] 5). By adopting the stacking and neutralization process, the corrosion of reaction equipment and operation safety risks caused by the strong oxidizing and corrosive properties of polybasic acid are overcome, the conventional dynamic chemical reaction mode is changed to a static reaction mode, the process flow is simplified, the production line is reduced, and the operation cost and safety risks are reduced;
[0043] 6). Acid-leach and extract heavy metal elements in solid waste and incorporate them into the high-aluminum molecular sieve for solidification, which not only realizes the full utilization of solid waste materials, but also enables hazardous waste elements to play a greater value in the adsorbent material. Description of the Drawings
[0044] Figure 1 It is a flow chart of the co-treatment and resource utilization process of industrial solid waste and CO2 in tail gas of the present invention. Detailed Embodiments
[0045] The present invention provides a co-treatment and resource utilization process of industrial solid waste and CO2 in tail gas, including the following steps:
[0046] Step 1): Mix the gasification slag, hydrochloric acid solution, sulfuric acid solution and nitric acid solution in sequence to obtain slurry 1, then mix the catalytic promoter and slurry 1 to obtain slurry 2, and then enhance the chemical reaction under the catalytic action of the surface activity of residual carbon and the assistance of the promoter, and successively carry out stacking and neutralization, washing and dissolution, and pressure filtration separation to obtain slag material 1 and mixed liquid 1;
[0047] The mixed solution 1 is a mixed solution containing aluminate and ferrate;
[0048] Step 2): First, use the ammonia replacement method to replace ferric hydroxide and heavy metal hydroxides in the mixed solution 1, raise the pH value to replace aluminum hydroxide precipitate and ammonium polyacid solution, heat-treat the aluminum hydroxide precipitate to make alumina products, or neutralize with hydrochloric acid to make aluminum chloride products;
[0049] Step 3): Pyrolyze the obtained ammonium polyacid solution to obtain ammonia gas and polyacid residual liquid. The ammonia gas is recycled for use in the ammonia replacement method in Step 2), and the polyacid residual liquid is recycled for use in the preparation of slurry 1;
[0050] Step 4): Perform the first alkali dissolution on the obtained slag 1, then sequentially perform water dissolution and pressure filtration separation to obtain a mixed solution 2 and slag 2;
[0051] The mixed solution 2 is a mixed solution containing sodium silicate and sodium tetrahydroxyaluminate;
[0052] Step 5): Perform the second alkali dissolution on the obtained slag 2, sequentially perform water dissolution and pressure filtration separation to obtain a mixed solution 3 and slag 3. The slag 3 is dried and activated to make activated carbon, and then used as a catalyst to be mixed with fly ash and / or coal gangue fine powder and recycled to Step 1);
[0053] The mixed solution 3 is a mixed solution containing sodium silicate;
[0054] Step 6): The mixed solution 2 reacts by absorbing carbon dioxide produced in the process tail gas, and is filtered to obtain solid 1 and sodium carbonate solution;
[0055] Solid 1 is a mixture of silicic acid and aluminum hydroxide;
[0056] Step 7): The mixed solution 3 reacts by absorbing carbon dioxide produced in the process tail gas, and is filtered to obtain silicic acid and sodium carbonate solution;
[0057] Step 8): Combine the sodium carbonate solutions obtained in Step 6) and Step 7), add calcium hydroxide for causticization reaction to obtain sodium hydroxide solution and calcium carbonate. The sodium hydroxide solution can be recycled, and the calcium carbonate is dried to make products;
[0058] Step 9): Hydrothermally synthesize and dry the silicic acid obtained in Step 7) to make silica products. Mix the mixture of silicic acid and aluminum hydroxide obtained in Step 6) with the heavy metal hydroxides obtained in Step 2) to prepare high-aluminum molecular sieves.
[0059] In the present invention, in step 1), first, hydrochloric acid solution is injected into the gasification slag. After stirring and mixing, sulfuric acid solution and nitric acid solution are then injected successively, so that the three acids are fully mixed with the gasification slag under stirring to form a thick slurry in a semi-fluid state, that is, slurry 1.
[0060] In the present invention, in step 1), the stacking and retting is to carry out static stacking and retting neutralization reaction by introducing a heat source for heating, which is a method of making the material and the solvent mixed into a paste-like semi-fluid state slurry and retting it in a sealed container in a static state;
[0061] During the stacking and retting process, the super strong acids react with aluminum oxide and iron oxide in the ash slag to be converted into soluble aluminates and ferrites during the static reaction, that is: 3H2SO4 + Al2O3 = Al2(SO4)3 + 3H2O;
[0062] 6HNO3 + Al2O3 = 2Al(NO3)3 + 3H2O; 6HCl + Al2O3 = 2AlCl3 + 3H2O;
[0063] 3H2SO4 + Fe2O3 = Fe2(SO4)3 + 3H2O;
[0064] 6HNO3 + Fe2O3 = 2Fe(NO3)3 + 3H2O;
[0065] 6HCl + Fe2O3 = 2FeCl3 + 3H2O.
[0066] In the present invention, in step 1), after the material is statically stacked and retted for a set time, it is exported and transported to a washing and dissolving device, and the reaction products aluminates solution and ferrites solution are dissolved out by washing with clear water.
[0067] In the present invention, in step 1), the mixed solution containing slag material, aluminates and ferrites obtained after washing with clear water is filtered by a plate and frame filter press to separate the aluminates and ferrites solution from the slag material, that is, slag material 1 and mixed solution 1.
[0068] In the present invention, the aluminates and ferrites solution can also be separated from the slag material by centrifugal dehydration and reverse osmosis membrane dehydration methods.
[0069] In the present invention, in step 2), the ammonia replacement method is to first adjust the pH value of the mixed solution 1 to ≤5, and first replace iron hydroxide and heavy metal hydroxides, and then raise the pH to the range of 5 - 9 to replace aluminum hydroxide and ammonium polyacid, that is:
[0070] Al2(SO4)3 + 6NH3·H2O = 2Al(OH)3 + 3(NH4)2SO4;
[0071] Fe2(SO4)3 + 6NH3·H2O = 2Fe(OH)3 + 3(NH4)2SO4;
[0072] Al(NO3)3 + 3NH3·H2O = Al(OH)3 + 3NH4NO3;
[0073] Fe(NO3)3 + 3NH3·H2O = Fe(OH)3 + 3NH4NO3;
[0074] AlCl3 + 3NH3·H2O = Al(OH)3 + 3NH4Cl;
[0075] FeCl3 + 3NH3·H2O = Fe(OH)3 + 3NH4Cl.
[0076] In the present invention, the heavy metal hydroxides include hydroxides such as mercury and nickel.
[0077] In the present invention, in step 2), the hydrochloric acid neutralization to produce aluminum chloride finished product is to add a hydrochloric acid solution with a preferably mass fraction of 15 - 25% to the aluminum hydroxide precipitate for reaction to convert it into aluminum chloride, that is, Al(OH)3 + 3HCl = AlCl3 + 3H2O, and then add hydrochloric acid with a preferably mass fraction of 30 - 35% to the aluminum chloride solution to produce the common ion effect, promoting the rapid crystallization and precipitation of aluminum chloride.
[0078] In the present invention, in step 4), the reaction of the first alkali dissolution is:
[0079] SiO2 + 2NaOH = Na2SiO3 + H2O;
[0080] Al2O3 + 2NaOH + 3H2O = 2NaAl(OH)4.
[0081] In the present invention, in step 5), the reaction of the second alkali dissolution is:
[0082] SiO2 + 2NaOH = Na2SiO3 + H2O.
[0083] In the present invention, in step 5), the activated carbon is used as a catalyst and mixed with fly ash and / or coal gangue fine powder, and reused in step 1). It is treated by the stacking neutralization method or the row ramming neutralization method to dissolve out the aluminum and iron components to generate aluminate and ferrate, and then through washing and dissolution, replacement, solid-liquid separation, and alkali melting of silicon dioxide, the comprehensive utilization of fly ash and coal gangue fine powder is realized.
[0084] In the present invention, in step 6), the absorption of carbon dioxide is carried out in a counter - flush sleeve bubble absorber, and the reaction is: Na2SiO3 + CO2 + H2O = H2SiO3 + Na2CO3.
[0085] In the present invention, in step 7), the absorption of carbon dioxide is carried out in a recoil sleeve bubbling absorber, and the reaction is: 2NaAl(OH)4 + CO2 = 2Al(OH)3 + Na2CO3 + H2O;
[0086] Na2SiO3 + CO2 + H2O = H2SiO3 + Na2CO3.
[0087] In the present invention, in step 9), the silicic acid is hydrothermally synthesized to obtain metasilicic acid, and then dried to form a silicon dioxide product, that is, H2SiO3 → SiO2 + H2O.
[0088] In the present invention, in step 9), the causticization reaction is:
[0089] Na2CO3 + Ca(OH)2 = 2NaOH + CaCO3.
[0090] In the present invention, the high-aluminum molecular sieve is a molecular sieve with a content of aluminum hydroxide greater than that of silicon dioxide, and the particle diameter is preferably between 0.4 nm and 1 nm.
[0091] In the present invention, in step 1), the main components of the gasification slag include aluminum oxide and iron oxide;
[0092] According to the component contents of aluminum oxide and iron oxide in the gasification slag, the dosage of the acid is prepared by calculating the mass percentage of various acids consumed in converting aluminum oxide and iron oxide according to the chemical reaction formula;
[0093] The mass concentration of the hydrochloric acid solution is preferably 35-37%; the mass concentration of the sulfuric acid solution is preferably 50-98%; the mass concentration of the nitric acid solution is preferably 50-98%; the ratio of the hydrochloric acid solution, the sulfuric acid solution and the nitric acid solution is 5-15%: 5-15%: 70-90%, preferably 8-12%: 8-12%: 75-85%, and further preferably 10%: 10%: 80%.
[0094] In the present invention, the catalytic action of the surface activity of the residual carbon refers to that the abundant active sites on the surface of the residual carbon have the ability to accept electrons and donate electrons, and can generate electrochemical reactions.
[0095] In the present invention, the hydrochloric acid solution, the sulfuric acid solution and the nitric acid solution are added in turn according to the order of decreasing acidity of the hydrochloric acid solution, the sulfuric acid solution and the nitric acid solution.
[0096] In the present invention, in step 1), the catalytic promoter includes hydrogen peroxide solution and / or chlorine-containing oxyacid solution, preferably hydrogen peroxide solution and chlorine-containing oxyacid solution.
[0097] In the present invention, the mass concentration of the hydrogen peroxide solution is 27.5 - 40%, preferably 32 - 38%, and more preferably 35%; the concentration of the chlorine oxyacid solution is 25 - 30%, preferably 28%; the chlorine oxyacids in the chlorine oxyacid solution include one or more of HClO4, HClO3, HClO2, and HClO, preferably HClO4, HClO3, HClO2, and HClO;
[0098] The total amount of the hydrogen peroxide solution and the chlorine oxyacid solution accounts for 5 - 10% of the sum of the masses of the hydrochloric acid solution, sulfuric acid solution, and nitric acid solution, preferably 8%.
[0099] In the present invention, in step 1), the temperature of the heap retting and neutralization is 50 - 80°C, preferably 70°C; the time of the heap retting and neutralization is 8 - 12 h, preferably 10 h;
[0100] The washing and dissolution is washing and dissolution with clear water, and the water - material ratio is 3 - 5:1, preferably 4:1.
[0101] In the present invention, in step 2), the ammonia replacement method includes adding ammonia water or introducing ammonia gas, preferably introducing ammonia gas.
[0102] In the present invention, in step 2), when the aluminum hydroxide precipitate is heat - treated to obtain alumina products, γ - alumina is obtained when the heat - treatment temperature is 140 - 150°C, and the heat - treatment temperature is preferably 145°C;
[0103] α - alumina is obtained when the heat - treatment temperature is 900°C - 1200°C, and the heat - treatment temperature is preferably 1100°C;
[0104] The concentration of the hydrochloric acid solution in the hydrochloric acid neutralization reaction is ≥25 wt%, preferably 25 wt%.
[0105] In the present invention, in step 4), the reagent used for the first alkali dissolution is sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is preferably 20 - 42%.
[0106] In the present invention, in step 5), the reagent used for the second alkali dissolution is sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is preferably 30 - 42%.
[0107] In the present invention, in step 5), the volume ratio of the fly ash and / or coal gangue fine powder to the activated carbon is 1:0.2 - 0.5, and more preferably 1:0.3.
[0108] In the present invention, gasified slag is formed under the atmosphere of multiple conditions and multiple environments. In the reaction atmosphere of the fixed bed furnace, when the gasification temperature is lower than 1100°C, the silicate components in the coal ash cannot be completely decomposed, so it is difficult to extract the metal components. In the reaction atmosphere of the air-supplied fluidized bed furnace, when the gasification temperature is higher than 1450°C, the alumina and silica in the ash are sintered into mullite (3Al2O3+2SiO2) with strong chemical stability under this environment, becoming the insoluble components that restrict the separation and purification of the ash. Whether there are silicate phase components or mullite phase components in the ash, because they have a stable chemical structure and are not easily oxidized by ordinary oxidants, they need to be treated with oxidants with special functions to achieve the purpose of comprehensive utilization. The method adopted by the present invention is to dissolve the ash by polyacid to decompose the silicate and mullite therein into alumina, iron oxide, and silica, and then convert and extract them through acid dissolution and alkali dissolution again.
[0109] In the present invention, because the three acids react strongly when mixed at the same time, they need to be mixed in order of acidity from weak to strong, and a super strong oxidizing atmosphere is formed in an atmosphere fully mixed with gasified slag. The sulfuric acid, nitric acid, and hydrochloric acid are combined to form a composite acid with super strong oxidizing and corrosive properties, which is mixed with ash residue. Under the electrochemical action generated by the active sites on the surface of the ash residue carbon, the silicon-aluminum and silicon-iron bonds in the silicate components are quickly interrupted to destroy their chemical structure. At the same time, the high concentration of hydrogen ions in the polyacid can form stable complex particles with oxygen ions on the surface of aluminum oxide and iron oxide, thereby reducing the potential of metal ions, enhancing the reducing ability of metal particles, and facilitating the reaction in the direction of metal dissolution. In this reaction process, the aqua regia effect generated by the polyacid enhances the chemical potential energy of aluminum dissolution and iron dissolution, and improves the dissolution efficiency.
[0110] In the present invention, coal particles are rapidly cracked under high temperature conditions during the gasification reaction. This thermal cracking not only volatilizes volatile substances, but also gasifies most of the carbon elements into carbon monoxide in an atmosphere where the carbon reaches a reduced state. The remaining carbon residue relaxes its structural chain due to the high temperature and destroys the chemical bonds of the ash components, resulting in the breaking of the silicon-aluminum covalent bonds and silicon-iron covalent bonds in the ash. The aluminum, iron and silicon impurities in the carbon residue are extracted and dissolved through acid and alkali dissolution processes, so that the carbon residue particles form activated carbon with a developed pore structure.
[0111] In the present invention, due to its developed pore structure and large specific surface area, activated carbon has rich active sites formed by various functional groups on its surface. Under certain conditions, it has the characteristics of accepting and donating electrons and has an electrocatalytic function in chemical reactions. At the same time, in the chemical reaction process between gasification slag and polyacid, hydrogen peroxide, perchloric acid or chloric acid, chlorous acid, hypochlorous acid are proportionally added to the reaction. Because of their strong oxidizing property, they can provide oxygen atoms in the chemical reaction, enabling the hydrogen ions ionized from the polyacid and the oxygen ions ionized from the promoter to reach ionization equilibrium. Under the catalytic action of activated carbon, the electrochemical reaction exerts a greater effect.
[0112] In the present invention, although the aqua regia effect of the polyacid can enhance the oxidation reaction with metal ions, at the same time, due to the super strong oxidizing and corrosive properties of the polyacid, the corrosion resistance of the reactor is weakened during the reaction process, and poisonous gases such as HCl, SO2, NO2, etc. will be generated. Based on this, the method for extracting aluminum and iron in the present invention mixes and piles up the gasification slag and the polyacid in a container with high corrosion resistance by adopting the stacking and neutralization method, and makes it stand still and react in the form of retting. Because this reaction method, on the one hand, does not need to improve the reaction rate through dynamic stirring and solid-liquid collision, the disturbance frequency of the corrosion factor to the equipment is reduced, and on the other hand, the residual carbon in the composition of the gasification slag has a developed pore structure and a large specific surface area, which can buffer the intensity of the chemical reaction. At the same time, activated carbon has rich active sites. Under certain conditions, it can accept or donate electrons, promote the regulation and balance of the central electrons and coordination electrons of the reactants, change the electronic structure of the reactant molecules, and affect their reaction properties. Moreover, the active sites on the surface of activated carbon are more active under the action of the catalytic promoter, making the oxidation potential and conversion efficiency of the chemical reaction even higher.
[0113] In the present invention, because the stacking and neutralization reaction is a static reaction, the presence of activated carbon can, on the one hand, assist the chemical reaction and, on the other hand, resolve the extreme chemical ability in the reaction. Therefore, the strong corrosion risk of the equipment and facilities can be overcome.
[0114] In the present invention, the extraction of aluminum and iron from gasification slag is achieved by acid dissolution. The aluminum and iron components are originally impurity components in coal and are hidden in the residual carbon. When a polybasic acid with extremely strong oxidizing property reacts with it, due to the intense reaction intensity, HCl, SO2, and NO2 poisonous gases will be decomposed during the reaction. However, while the polybasic acid dissolves the aluminum and iron components, it also leaves cavities in the coal particles. These cavities have strong polarity, well-developed pore structures, and strong dispersion forces, so they have strong adsorption capacity. Since the chemical reaction occurs inside the stacked reactants first, the poisonous gases generated diffuse from the inside to the outside. The pore structure inside the residual carbon has the conditions and advantages for preferential adsorption. Therefore, most of the poisonous gases are adsorbed by the adsorption function of the activated carbon itself, and then dissolved and converted into a new solvent through the water-soluble desorption function, making it have both the function of adsorbing and removing toxins and the function of regenerating the solvent.
[0115] In the present invention, the ammonia replacement is a reaction in which ammonium ions replace the reaction products aluminate and ferrate. The slurry mixture of slag material, aluminate, and ferrate is filtered by a plate and frame filter press to filter out the aluminate and ferrate solutions, separating the solution from the slag material. Ammonia gas or ammonia water is introduced into the clear aluminate and ferrate solution to adjust the pH value. Through practical observation, when the solution temperature is controlled at 25 - 50 °C and ammonia water is injected into the mixed solution of polybasic acid aluminum and polybasic acid iron, when the pH of the mixed solution = 5, brown crystals precipitate. Through analysis, the main component of this crystal is iron hydroxide. When the pH value is raised to 5 - 9, the color of the precipitated crystals is light green. Through analysis, the main component of this crystal is aluminum hydroxide. This shows that when the temperature of the mixed solution is maintained at 25 - 50 °C and ammonia water is added to the solution to adjust the pH value, when the pH value of the solution is less than or equal to 5, iron hydroxide in the mixed solution is precipitated, and when the pH value of the solution is increased to greater than 5 and less than 9, aluminum hydroxide in the solution is precipitated. Therefore, taking pH = 5 as the dividing line for separating iron hydroxide and aluminum hydroxide from the mixed solution of aluminate and ferrate, controlling the pH value of the solution to achieve the separation of iron hydroxide and aluminum hydroxide.
[0116] In the present invention, aluminum hydroxide is obtained by replacing the aluminate solution through an ammonia replacement reaction. The aluminum hydroxide is dried at a temperature of 140 - 150 °C to form γ-aluminum oxide, and calcined at a temperature of 900 - 1200 °C to form α-aluminum oxide. Since the generated aluminum hydroxide precipitate has small particle size and high viscosity, it is difficult to filter and dry in subsequent processing, and it is not easy to process it by conventional filtration and drying methods. Therefore, in addition to producing aluminum oxide by drying and calcining aluminum hydroxide, the present invention also uses the hydrochloric acid conversion method to convert aluminum hydroxide into aluminum chloride, and then dehydrates and dries it to produce aluminum chloride products.
[0117] In the present invention, aluminum hydroxide is displaced by decomposing polybasic acid aluminum. Due to the existence of crystal water, aluminum hydroxide has special physical and chemical properties. Its small particle size and high crystal water content result in high viscosity of the material, which makes it difficult to process in subsequent treatments and narrows the application market of the product. When it is made into γ-aluminum oxide, although the process is simple (only ordinary drying is required) and the energy consumption is small (formed at a temperature of 140-150 °C), the physical properties of the product are greatly defective (small particle size and low density), the application range is narrow, and the market prospect is dim. When it is made into α-aluminum oxide, although the application range is wide, the production process is complex and the energy consumption is large. Therefore, the present invention preferably converts part of the aluminum hydroxide into aluminum chloride products by the hydrochloric acid conversion method, and dries and calcines part of the aluminum hydroxide to make aluminum oxide.
[0118] In the present invention, the ammonium ions in the polybasic acid ammonium solution (a mixed solution of ammonium sulfate, ammonium chloride, and ammonium nitrate) are weakly basic ions and cannot be completely ionized. Therefore, there is hydrated ammonia in the polybasic acid ammonium solution. Since the hydrated ammonia has the situation of ammonia molecule escape when heated to above 90 °C, the escaped ammonia molecules are carried out through the ammonia escape channel, thus destroying the ionization equilibrium of the polybasic acid ammonium solution and making the reaction proceed in the direction of ammonia escape, and more ammonia molecules are carried out, so that a solution containing dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid is finally obtained. Therefore, dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid can be obtained by ammonia evaporation from the polybasic acid ammonium solution, and its decomposition method conforms to the principle of chemical reaction equilibrium.
[0119] Regarding the decomposition temperature of the polybasic acid ammonium solution, practice has proved that when impurities are present, the thermal decomposition mechanism of ammonium nitrate below 150 °C is: 4HNO3→4NO2+2H2O+O2;
[0120] NH4NO3+2NO2→N2+H2O+HNO3;
[0121] The influence mechanism of acid on the ammonium nitrate decomposition reaction is:
[0122]
[0123] NO2 + +NH3→NH3NO2 + →N2O+H3O + .
[0124] Therefore, H2SO4, HNO3, HCl, etc. can accelerate the decomposition of ammonium nitrate, ammonium sulfate, and ammonium chloride. The main promoting effect of single acid on ammonium salts is to lower the initial decomposition temperature of ammonium salts; the ammonium chloride and ammonium nitrate in the polybasic acid ammonium decompose thermally in the form of autocatalytic reactions. It can be seen that acid can make ammonia molecules and dilute sulfuric acid, dilute nitric acid, and dilute hydrochloric acid generated from ammonium sulfate, ammonium nitrate, and ammonium chloride solutions at a relatively low temperature (above 90 °C). Accordingly, since ammonium sulfate and ammonium nitrate, ammonium chloride solutions are weakly acidic, a small amount of H is contained in their solutions+ and with the continuous removal of ammonia molecules, it positively promotes the decomposition reactions of ammonium sulfate, ammonium nitrate, and ammonium chloride solutions, and then a solution containing dilute sulfuric acid, dilute nitric acid, and dilute hydrochloric acid is obtained.
[0125] Specifically, the ammonium polyacid solution contains ammonium ions, sulfate ions, nitrate ions, and chloride ions. In a liquid environment, the density of ammonium ions is less than that of other polyacid root ions, resulting in the easy volatilization of ammonium ions when heated. Through practical observation, when the ammonium polyacid is heated above 90 °C, gaseous ammonia escapes with water vapor, and the gas is alkaline with a pH value greater than 7. When a certain amount of gas escapes, the gas approaches neutrality, while the remaining liquid is acidic with a pH value less than 7; however, if the concentration of the ammonium polyacid solution increases to supersaturation due to the evaporation of water, the ammonium polyacid precipitates in crystal form, and the decomposition stops at this time. Through chemical analysis, when the ammonium polyacid solution is heated below the saturated solubility, the alkaline molecules escaping with water vapor are ammonia molecules, and the components remaining in the liquid are sulfuric acid, nitric acid, and hydrochloric acid. This shows that: when the ammonium polyacid solution is heated above 90 °C and can always maintain the dynamic equilibrium of the ammonium polyacid solution concentration less than the supersaturated solubility, the ammonium polyacid solution can decompose. During the decomposition process, the alkaline molecules escaping with water vapor are ammonia molecules, and the acidic components remaining in the water are polyacids.
[0126] In the thermal decomposition process, the ammonium polyacid generated by the displacement reaction is heated to above 90 °C in a pyrolyzer. While maintaining the ammonium polyacid solution continuously less than the supersaturated solubility, the escaped ammonia gas is introduced into the ammonia displacement system for use through a pipeline, and the polyacid in the residual liquid is returned to the aluminum melting process after being adjusted. This invention realizes the recycling of waste gas and waste liquid.
[0127] In the present invention, the amount of silicon dioxide to be extracted is determined according to the content of residual alumina in the residue after acid leaching for aluminum extraction. Sodium hydroxide required for the reaction is calculated according to the molar ratio of alumina to silicon dioxide of 1:1 and a solution is prepared. The prepared sodium hydroxide solution is mixed with the residue, and the solid and liquid materials are uniformly mixed in a stirrer to form a semi-fluid slurry. The mixed slurry is introduced into a stacking reactor through a delivery pump and left to react for 8 - 12 hours. Under the catalytic promotion of activated carbon in the residue, sodium hydroxide dissolves alumina to form sodium aluminate and dissolves silicon dioxide to form sodium silicate. The clinker after the reaction is sent to a silicon extraction washing and dissolving device, and the washing, thickening separation, and plate and frame filtration in the aluminum melting process are repeated. The clear liquid is introduced into an acid ion exchanger to absorb carbon dioxide in the dry tail gas to decompose sodium aluminate and sodium silicate to displace aluminum hydroxide, silicic acid, and sodium carbonate. Aluminum hydroxide and silicic acid are filtered through a plate and frame filter. After filtering out the sodium carbonate clear liquid, calcium hydroxide is reacted through a causticization reaction to form calcium carbonate and sodium hydroxide. Calcium carbonate is made into a by-product, and sodium hydroxide is recycled.
[0128] In the present invention, the filter cake obtained by pressure filtration in the silicon dissolution process is fed into the second silicon dissolution process, and the filter cake obtained by pressure filtration after acid ion exchange is made into molecular sieve hollow particle products.
[0129] In the present invention, the silica content of the residue from the first silicon dissolution is analyzed, and the amount of sodium hydroxide required for silicon dissolution is calculated according to the amount of residual silica by relative molecular mass, and a sodium hydroxide solvent is prepared. Through mixing, the first silicon dissolution process is repeated, the generated liquid is separated from the residue, and then separated by a thickener, plate and frame pressure filtration. The mixture that has completed the reaction is washed with clear water to dissolve the sodium silicate solution, and then the sodium silicate solution is filtered out by a plate and frame filter press to be separated from the filter cake. The remaining solid residue carbon in the filter cake is washed with clear water to wash out the remaining residual salt, and then dried and activated to make activated carbon or added to the comprehensive utilization process of fly ash and gangue for repeated use. The sodium silicate clear liquid filtered out by pressure filtration completes acid ion exchange by absorbing carbon dioxide in the process tail gas to displace silicic acid and sodium carbonate. Because of the different conditions for the formation of silicic acid, it exists in the form of orthosilicic acid. The surface network structure of the orthosilicic acid crystal is loose, in the form of small molecules, and the structure is unstable. It is soluble in water and acid solutions. In order to optimize and improve its material properties, in the present invention, it is transformed into metasilicic acid in a boiling environment above 102 °C by hydrothermal synthesis method, and then dehydrated and dried to make silica products.
[0130] In the present invention, during the gasification reaction of coal, the coal particles are rapidly pyrolyzed under high-temperature conditions. This thermal pyrolysis not only volatilizes volatile substances, but also gasifies most of the carbon elements into carbon monoxide in an atmosphere where carbon reaches the reduced state. The residual carbon residue has its structural chain loosened due to high temperature, and the chemical bonds of the ash components are broken, resulting in the breaking of silicon-aluminum covalent bonds and silicon-iron covalent bonds in the ash. Through the processes of acid leaching for aluminum extraction and alkali leaching for silicon extraction, the aluminum, iron, and silicon impurities in the carbon residue are extracted and dissolved, and a double impregnation of acid and alkali is formed, making the carbon residue particles form an activated carbon with a well-developed pore structure.
[0131] In the present invention, due to its well-developed pore structure and large specific surface area, activated carbon has rich active sites formed on its surface due to the presence of various functional groups. Under certain conditions, it has the characteristics of accepting electrons and donating electrons, and has an electrochemically catalytic function in chemical reactions. At the same time, during the chemical reaction between the gasification slag and the polyacid, hydrogen peroxide, perchloric acid or chloric acid, chlorous acid, hypochlorous acid are proportionally added to the reaction. Because of its strong oxidizing property, it can provide oxygen atoms in the chemical reaction and can promote the catalytic activity of activated carbon in the chemical reaction of acid leaching aluminum and iron from the gasification slag, enabling the electrochemical reaction to play a greater role in the acid leaching of aluminum and iron.
[0132] In the present invention, due to the excellent catalytic function of activated carbon, an electrochemical boosting effect is generated in the materials and reactions, and under the promotion of strong oxidants such as hydrogen peroxide, the potential energy of chemical reactions is further enhanced. Therefore, the composting neutralization method has the advantages of strong dissolution power and high reaction rate in the chemical reaction for extracting high-valent metal components from powder solid waste. Due to different formation pathways of gasification slag, the inherent carbon residue is a catalytic carrier. By impregnating the inherent catalytic carrier with acid and alkali, its pore structure becomes more developed and the active sites become more abundant. After multiple impregnations, the activity of the carrier becomes stronger. Therefore, the carbon residue after leaching aluminum and silicon from gasification slag is used as a catalytic carrier in the comprehensive utilization of fly ash and coal gangue powder, making it easier to achieve acid leaching of aluminum and alkali leaching of silicon.
[0133] In the present invention, fly ash is a powder solid waste intercepted after coal combustion and dust removal. During the generation process, most of the silicate components in the ash are decomposed by combustion, but there are still a small number of undecomposed silicate components and some mullite components formed by high-temperature sintering. Since the chemical structures of silicate and mullite components are stable and ordinary oxidants cannot break their chemical bonds, it is very difficult to transform them. Therefore, a super strong oxidant combined with a catalyst is needed to decompose them into ordinary oxides and then carry out transformation and extraction. Therefore, the super strong oxidation function of polybasic acid is combined with the electrochemical function of the activated carbon catalytic carrier and the assistance of a promoter to first decompose them into ordinary oxides and then dissolve and transform them into soluble salts, so as to achieve acid leaching of aluminum and iron from fly ash.
[0134] In the present invention, since coal gangue powder has not undergone high-temperature combustion and its main component is silicate with a very stable chemical structure, it can only be decomposed and transformed under the action of a super strong oxidant and a more active catalyst. The carbon residue in gasification slag has a very developed pore structure and abundant active sites after one-step acid-base impregnation during the process of leaching aluminum and silicon. Under the dual action with super strong acid, it can easily break the chemical bonds of the undecomposed silicate in fly ash, making it easy to achieve acid leaching of aluminum and silicon from fly ash. After acid leaching and alkali leaching of gasification slag, the separated carbon residue is added to fly ash and then acid leached and alkali leached again. After multiple impregnations, the activity of the carrier becomes stronger, the active sites become more abundant, and the generated electrochemical energy is higher, so the chemical transformation of coal gangue can be achieved. Based on this, in the present invention, the carbon residue of gasification slag is continuously used in the dissolution and transformation of powder solid waste, and the treatment sequence of the three solid wastes is arranged as gasification slag → fly ash → coal gangue powder, so as to achieve the comprehensive utilization of powder solid waste.
[0135] In the present invention, the residual carbon particles in the gasification slag are reciprocally impregnated with acid and alkali through the above-mentioned acid dissolution and alkali dissolution treatments. The residual carbon originally subjected to gasification pyrolysis has a loose network structure and a well-developed pore structure. After acid impregnation, the metal components in the impurities are dissolved out, and after alkali impregnation, the siliceous components in the impurities are dissolved out. The acid and alkali impregnations turn it into a porous material with a very well-developed pore structure and a huge specific surface area, and at the same time, it has abundant active sites. Under certain conditions for participating in chemical reactions, it can accept or donate electrons, promote the regulation and balance of the central electrons and coordination electrons of the reactants, change the electronic structure of the reactant molecules, and affect their reaction properties. Moreover, the active sites on the surface of the activated carbon will increase the contact momentum between the reactants under the action of the strong divergence of the catalytic promoters H2O2, HClO4 or HClO3, HClO2, HClO, thereby increasing the reaction rate. Its various catalytic activities act as catalysts that can improve the reaction efficiency in the composting reaction and can play a role in catalytic activation and promotion of chemical reactions under the action of the promoters. Therefore, in the presence of activated carbon catalysis and promoters, the reaction rate of the composting neutralization reaction will be higher. Based on this, the present invention takes the comprehensive treatment of gasification slag as the prior basis for the comprehensive treatment of fly ash and coal gangue powder, and uses the residual slag activated carbon after the treatment of gasification slag as the catalytic carrier for the aluminum and silicon extraction reactions of fly ash and coal gangue powder. With the assistance of the catalytic promoters H2O2, HClO4 or HClO3, HClO2, HClO, the reaction activity is enhanced and the reaction efficiency is improved.
[0136] In the present invention, the mechanical device for mixing and stirring used in the experiment is preferably a star-shaped stirrer. The stirring device is divided into two systems: a revolution system and a rotation system. The rotation system rotates around the revolution shaft driven by a chain or gear on the revolution shaft to loosen the stirring channel of the revolution boom, reduce the torque load of the boom stirring, and improve the stirring efficiency of the materials.
[0137] In the present invention, the material washing and dissolving device used in the experiment is an inverted cone device arranged in rows. A rotary stirrer is installed inside the washing and dissolving device, and it has a feed inlet, a water inlet, an overflow outlet, a discharge outlet, and a steam heating pipeline.
[0138] In the present invention, the thickener used in the experiment is an inverted cone container with a relatively large cross-sectional diameter. A central sleeve configured in a certain proportion is installed in the center. The upper part of the sleeve protrudes above the upper edge of the thickener, and the bottom of the sleeve reaches the variable diameter part of the cylinder and the cone of the thickener.
[0139] In the present invention, during the acid dissolution and transformation process of gasification slag, not only alumina and iron oxide are dissolved and transformed, but also the contained trace heavy metal elements are dissolved and transformed. Common heavy metal elements in gasification slag include nickel, mercury, lead, etc., which are transformed into salts mainly composed of nickel chloride, mercury chloride, lead chloride, etc. in acid dissolution. Since the solubility of these salt solutions is extremely low, they are replaced by nickel hydroxide, mercury hydroxide, lead hydroxide and other hydroxides prior to the decomposition of ferrite in the displacement reaction. Also, since the density of these hydroxides is much greater than that of iron hydroxide, they will settle and accumulate at the bottom of the container prior to iron hydroxide due to gravity during sedimentation. Therefore, they are separated and extracted by the density difference separation method.
[0140] In the present invention, the density difference separation is achieved through a thickener. The hydroxide mixture slurry is introduced into the upper opening of the central sleeve and enters the bottom of the thickener. The continuously increasing mixed liquid turns back at the bottom of the sleeve and rises from bottom to top outside the sleeve. During the rising process, the solids in the liquid settle under the action of their own gravity. The heavy metal hydroxides sink quickly due to their large density and first accumulate in the cone at the bottom of the thickener. After standing for a certain time, they are discharged from the discharge port.
[0141] In the present invention, since heavy metal hydroxides are hazardous waste substances with high environmental risks and narrow application areas, they cannot be used without solidification treatment. Also, due to their cationic properties, the present invention makes them into foam molecular sieve adsorption bricks. Because of their cationic properties, they have an adsorption advantage for acidic molecules and can reflect their unique value and advantages in the adsorption bricks, thus optimizing their utilization.
[0142] In the present invention, fly ash is a powdery solid waste intercepted by dust removal after coal combustion. During the generation process, most of the silicate components in the ash are decomposed by combustion, but there are also a small part of undecomposed silicate components and some mullite components sintered at high temperature. Coal gangue is not burned at high temperature, and its material composition structure is mainly silicate. Since the chemical structures of silicate and mullite components are stable and ordinary oxidants cannot break their chemical bonds, it is very difficult to transform them. Therefore, a super strong oxidant combined with a catalyst is needed to decompose them into ordinary oxides and then carry out transformation and extraction. Therefore, the super strong oxidation function of polybasic acid is combined with the electrochemical function of activated carbon catalytic carrier and the assistance of a promoter to first decompose them into ordinary oxides and then dissolve and transform them into soluble salts, so as to achieve the acid dissolution of fly ash and coal gangue to extract aluminum and iron. Based on this, in the present invention, the three kinds of waste residues are synergistically treated by the method of row ramming and neutralization. Through this method, the reaction intensity of acid dissolution of aluminum and iron and alkali dissolution of silicon dioxide is promoted, and the residual carbon of gasification slag is continuously used in the process of dissolving and transforming the powdery solid waste, forming a synergistic effect in the treatment processes of the three kinds of solid wastes, and making the comprehensive utilization of industrial bulk solid wastes form a large cycle, large combination and large connection chain.
[0143] The technical solutions provided by the present invention will be described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0144] Example 1
[0145] Pilot project on the collaborative treatment and resource utilization of industrial waste gasification slag, fly ash, coal gangue and carbon dioxide in the waste gas in the Tuke Industrial Park, Wushenqi, Inner Mongolia.
[0146] Pilot project completion unit: Longyuan (Beijing) Environmental Protection Technology Co., Ltd., Pilot project time: from early August 2024 to the end of January 2025, Pilot project method: scaled-up intermediate experiment from laboratory results to industrial application.
[0147] Pilot project content:
[0148] 1. Selection and preparation of polyacids;
[0149] 2. Extraction and purification of aluminum oxide and silicon dioxide in the mixture of coarse and fine gasification slag;
[0150] 3. Transformation and utilization of residual carbon in gasification slag;
[0151] 4. Product processing of various products.
[0152] Pilot project purpose:
[0153] 1. Try the preparation methods and positive and negative effects of polyacids, determine the efficacy and advantages of polyacids in extracting aluminum and iron from gasification slag, and solve the safety risks of strong corrosion of polyacids in use.
[0154] 2. Compare the advantages and disadvantages of two chemical reaction methods, namely liquid-phase dissolution and stacking neutralization, in the reactions of dissolving aluminum and silicon in gasification slag, and summarize the best solution suitable for the comprehensive utilization of gasification slag.
[0155] 3. Select the transformation methods and end products of each component in gasification slag;
[0156] 4. Obtain the extraction rate and conversion rate data of each component in gasification slag;
[0157] 5. Verify the effects of the aqua regia effect, catalytic carrier, and promoter of polyacids in extracting metal components from gasification slag, observe the reaction state of the solid-liquid two-phase state during the stacking neutralization reaction, and the change of ion diffusion characteristics under this state;
[0158] 6. Select the best facilities for each process and master the functions and advantages of each facility;
[0159] 7. Determine the reaction method, reaction time, and reaction temperature, and summarize the adjustment of reaction time and reaction temperature under this method;
[0160] 8. Master the pH value change range in each reaction stage;
[0161] 9. Determine the method of solid-liquid separation of the reaction products and the optimal separation plan;
[0162] 10. Determine the best method for the double decomposition of polyaluminum acid and the process route for the purification and productization of the reaction products;
[0163] 11. Compare the advantages of the three products of aluminum hydroxide, alumina, and aluminum chloride and the best adaptability of the process flow;
[0164] 12. Treatment and utilization of waste residues and waste liquids.
[0165] Pilot run process:
[0166] The pilot project selects the gasification slag generated from the coal chemical deep processing process of xxx Energy Co., Ltd. in the Tuke Chemical Industrial Park, Wushenqi, Inner Mongolia as the raw material, with 1 ton as 1 base unit. Composition of gasification slag: Al2O3 = 15%, Fe2O3 = 5%, SiO2 = 20%, C = 25%, heavy metal components: HgO, NiO less than 0.2%, other components including CaO, MgO, Na2O less than 2%, H2O = 33%, then Al2O3 = 0.15t, Fe2O3 = 0.05t, SiO2 = 0.2t, C = 0.25t, heavy metal components: HgO, NiO less than 0.002t, other components including CaO, MgO, Na2O less than 0.02t, H2O = 0.33t.
[0167] According to the chemical reaction formula:
[0168] 3H2SO 4(74.6%) +Al2O 3(25.4%) =Al2(SO4) 3(86.4%) +3H2O (13.6%)
[0169] 3H2SO 4(64.75%) +Fe2O 3(35.25%) =Fe2(SO4) 3(88%) +3H2O (12%)
[0170] It is obtained that in 1 ton of mixed raw materials, there is Al2O3 = 0.15 ton, with an extraction rate of 90%, that is, 0.135 ton; Fe2O3 = 0.05 ton, with an extraction rate of 90%, that is, 0.045 ton; in the solvent polyacid, it contains 10% sulfuric acid, 10% nitric acid, and 80% hydrochloric acid. Then: To extract alumina, it is necessary to consume H2SO4 = 0.3966 ton, and generate Al2(SO4)3 = 0.459 ton; consume HNO3 = 0.5 ton, and convert to generate Al(NO3)3 = 0.564 ton, and it is necessary to consume HCl = 0.2899 ton, and convert to generate AlCl3 = 0.3533 ton; To convert iron oxide, it is necessary to consume H2SO4 = 0.0827 ton, and generate Fe2(SO4)3 = 0.1123 ton, consume HNO3 = 0.1081 ton, and convert to generate Fe(NO3)3 = 0.1384 ton, consume HCl = 0.0616 ton, and convert to generate FeCl3 = 0.0914 ton.
[0171] Convey the gasified slag into the mixing and stirring container through a screw conveyor. At the same time, first introduce a hydrochloric acid solution with a concentration of 35% into the container through an acid pump. The slag material and the hydrochloric acid solution are mixed under the agitation of the stirrer. After the hydrochloric acid solution and the slag material are evenly mixed, then introduce a 50% sulfuric acid solution and a 50% nitric acid solution in sequence. The ratio of various acids is calculated and added according to the relative molecular masses of alumina and iron oxide in the slag material. That is: In 1 ton of mixed raw materials, there is Al2O3 = 0.15 ton, with an extraction rate of 90%, that is, 0.135 ton; Fe2O3 = 0.05 ton, with an extraction rate of 90%, that is, 0.045 ton; in the solvent polyacid, it contains 10% sulfuric acid, 10% nitric acid, and 80% hydrochloric acid. Then: To extract alumina, it is necessary to consume H2SO4 = 0.0396 ton, and generate Al2(SO4)3 = 0.0459 ton, and it is necessary to consume HNO3 = 0.05 ton; convert to generate Al(NO3)3 = 0.0564 ton, and it is necessary to consume HCl = 0.0298 * 8 = 0.2384 ton, and convert to generate AlCl3 = 0.03533 * 8 = 0.2826 ton; To extract iron oxide, consume H2SO4 = 0.0082 ton, and generate Fe2(SO4)3 = 0.0112 ton; consume HNO3 = 0.0106 ton, and convert to generate Fe(NO3)3 = 0.0136 ton; consume HCl = 0.00616 * 8 = 0.0488 ton, and convert to generate FeCl3 = 0.0091 * 8 = 0.0728 ton. Based on 1 ton of gasified slag raw material as the base, add 0.0792 ton of 50% sulfuric acid, add 0.1 ton of 50% nitric acid, and add 0.139 ton of 35% hydrochloric acid.
[0172] After mixing acid and slag to form a semi-fluid slurry 1, a mixed solution prepared by mixing H2O2 with a concentration of 30% and HClO4 with a concentration of 25% is introduced into the slurry 1 as a catalytic promoter. Due to the super strong oxidizing property of the promoter, when it is mixed with the material, its dispersing function causes the material to expand under the push of bubbles. When the dispersing force of the promoter gradually weakens and the foaming trend of the mixed slurry gradually decreases, the slurry is successively introduced into each retting container through a slurry transfer pump. When the liquid level of the slurry rises to the two-thirds water level scale of the container, the feeding is stopped, and then the screw cap is tightened to seal the container. The material continuously releases heat due to chemical reactions in the retting container until the material temperature reaches 70°C. Since the heat release of the material reaches the peak value during the reaction indicating the most intense reaction, external heat heating is started when the material temperature begins to drop, so that the temperature in the container is always maintained at 60 - 80°C. After the acid and slag are mixed, the pH value of the initial liquid material is less than 1, and the material reaction continues, and the pH value continuously increases. When the pH value of the liquid material rises to 4, the reaction is basically completed. The bucket cover is unscrewed, and a small amount of hot water is injected into the container. By stirring and mixing, the fluidity of the slurry is enhanced, and then the slurry in the retting container is transported to the material washing and dissolving device through a slurry transfer pump.
[0173] The slurry is injected from the feed inlet of the material washing and dissolving device, and at the same time, clear water is introduced into the container to mix the clear water with the slurry. The solid-liquid ratio of the clear water to the slurry is 3:1. The slurry and the clear water continuously enter in proportion. The rotary stirrer is started to rotate reversely to make the slurry stir in a floating state. The slurry and the clear water are continuously injected. After being filled, it overflows through the overflow port to the next container. The overflow port of the first washing and dissolving device is connected to the feed inlet of the second washing and dissolving device through a pipeline. The liquid material overflowing from the overflow port flows into the next washing and dissolving device along the pipeline, flowing one by one in this way. During this process, the clear water continuously dilutes and dissolves the material in each washing and dissolving device. To enhance the water-soluble ability, the slurry in the washing and dissolving device is heated by steam to maintain the temperature. After the slurry is washed through several washing and dissolving devices, the soluble substances are dissolved, and the slurry overflowing from the last washing and dissolving device is introduced into the thickener through a transfer pump.
[0174] The mixed slurry enters from the upper opening of the central sleeve to the bottom of the thickener. The continuously increasing mixed liquid turns back at the bottom of the sleeve and rises from bottom to top outside the sleeve. During the rising process, the solids in the liquid material settle under the action of their own gravity. The solids continuously settle, and the clear liquid continuously floats up. When the clear liquid floats up to the overflow port on the upper edge of the thickener, it flows through the conduit to the clear liquid collection container for subsequent replacement treatment. The settled solids gather at the bottom cone of the thickener and are intermittently discharged and then filtered by a plate and frame filter press to separate the solid and liquid, obtaining slag material 1 and mixed liquid 1.
[0175] The clear liquid separated by the thickener is a mixed solution of aluminum polyacid and iron polyacid. The ammonia replacement method is used to separate the two components by adjusting the pH value. In the replacement reactor, first fill the reactor with the mixed clear liquid of aluminate and ferrate, then add ammonia water or ammonia gas from the central sleeve and start the stirring device. The ammonium ions in the ammonia water react with the acid radicals in the aluminate and ferrate in the mixed solution to form ammonium salts. The aluminate and ferrate are decomposed, and the metal ions are displaced and exist in the form of hydroxides. Since the solubility of the ferrate solution is less than that of the aluminate, iron hydroxide is formed prior to aluminum hydroxide. When the solution pH value is controlled to be less than or equal to 5, brown iron hydroxide is formed and settles. When the generated substances continuously decrease and no longer generate, the sediment is discharged and collected from the bottom discharge port, and then ammonia water or ammonia gas is slowly added into the central sleeve. When the solution pH value continuously rises, precipitation occurs and slowly settles. At this time, the color of the sediment gradually changes from brown to light green, and the generated precipitate is aluminum hydroxide. When the solution pH value rises to 9, the replacement reaction stops, and the separated solid is aluminum hydroxide, and the component retained in the clear liquid is ammonium polyacid.
[0176] The ammonium polyacid is heated and decomposed in the ammonium evaporator to separate ammonia from the polyacid and recycle it, so as to finally obtain a solution containing dilute sulfuric acid, dilute hydrochloric acid and dilute nitric acid. Therefore, dilute sulfuric acid, dilute hydrochloric acid and dilute nitric acid can be obtained by ammonia evaporation from the ammonium polyacid solution, and its decomposition method conforms to the principle of chemical reaction equilibrium.
[0177] In the thermal decomposition process, the ammonium polyacid generated by the replacement reaction is heated to 95 °C in the pyrolyzer (to avoid the volatilization of hydrogen chloride gas when the hydrochloric acid solution temperature is greater than 100 °C), and the ammonium polyacid solution is kept continuously less than the supersaturated solubility. The escaped ammonia gas is introduced into the ammonia replacement system for use, and the polyacid in the residual liquid is returned to the aluminum dissolution process after modulation.
[0178] Dissolve the aluminum hydroxide precipitate with 25wt% dilute hydrochloric acid to convert it into a saturated aluminum chloride solution. Lower the temperature of the saturated aluminum chloride solution to the supersaturated critical point, and then add 35wt% concentrated hydrochloric acid to the aluminum chloride solution to produce the common ion effect in the reaction between hydrochloric acid and aluminum chloride. Under the action of the common ion effect, the solubility of the aluminum chloride solution decreases sharply, and the solubility of aluminum sulfate and aluminum nitrate increases correspondingly, and aluminum chloride precipitates within a certain range. The aluminum chloride is made into a finished product through centrifugal dehydration and drying.
[0179] The remaining components in the residue after acid dissolution for extracting aluminum and iron are mainly residual carbon, unreacted alumina (10%) and silicon dioxide. The quantity of silicon dioxide to be extracted is determined proportionally based on the amount of alumina in the residue. Since the end product of the reaction is a high-alumina molecular sieve which requires a ratio of alumina to silicon dioxide greater than 1:1, the quantity of sodium hydroxide required for alumina and silicon dioxide to be greater than 1:1 is calculated through relative molecular mass. Sodium hydroxide is formulated into a 20% mass fraction solution and mixed with the slag material in a star-shaped stirrer to make a semi-fluid slurry, which is then introduced into a stacking and neutralizing reactor and left standing for the first alkali dissolution. Sodium hydroxide dissolves alumina to form sodium aluminate and dissolves silicon dioxide to form sodium silicate, that is: Al2O3 + 2NaOH = 2NaAlO2, SiO2 + 2NaOH = Na2SiO3 + H2O.
[0180] Dissolving 0.0135 tons of alumina requires 0.01 tons of sodium hydroxide and produces 0.021 tons of sodium aluminate; dissolving 0.018 tons of silicon dioxide requires 0.024 tons of sodium hydroxide and produces 0.0366 tons of sodium silicate. After the mixture is left standing and reacting for 9 hours, it is injected with hot water for dilution, and then introduced into a silicate washing and dissolving device. The steps of washing and dissolving polyaluminum acid are repeated to dissolve the sodium tetrahydroxyaluminate and sodium silicate formed after the reaction into a mixed solution, which is then thickened and separated by a thickener and separated by plate-and-frame filtration to obtain slag material 2 and mixed solution 2.
[0181] The mixed solution 2 absorbs carbon dioxide in the process tail gas in a carbonation reactor for an ion exchange reaction to displace aluminum hydroxide, silicic acid and sodium carbonate (that is: 2NaAlO2 + CO2 + 3H2O = 2Al(OH)3 + Na2CO3, that is: 0.021 tons of sodium aluminate reacts with 0.0056 tons of carbon dioxide to produce 0.0199 tons of aluminum hydroxide and 0.0135 tons of sodium carbonate). The resulting solution is then thickened and separated by a thickener and separated by plate-and-frame filtration to separate the two solids of aluminum hydroxide and silicic acid from the sodium carbonate solution. Sodium carbonate and calcium hydroxide are used in a causticization reaction to produce sodium hydroxide and calcium carbonate. Sodium hydroxide is recycled for silicon dissolution of the slag material, and calcium carbonate is dried to make a powder product.
[0182] The aluminum hydroxide and silicic acid filter cakes filtered out by plate-and-frame contain crystal water and have a fine particle size. Under the state of vibration or agitation, part of the crystal water will break away from the crystal and become free water. Therefore, in this embodiment, the heavy metal hydroxides separated by the aforementioned density difference separation process are mixed with the filter cake to make a foam adsorption brick.
[0183] After the first strong alkali melting reaction, the remaining alumina (10% of the total amount = 0.0135t) and part of the silica (in a 1:1 ratio with alumina, i.e., 0.0135t) are dissolved, and the remaining slag 2 mainly consists of residual carbon and silica. The slag 2 (the amount of silica in the first alkali dissolution: 0.18t - 0.0135t = 0.1665t) is mixed with sodium hydroxide according to the ratio calculated by relative molecular mass (i.e., 0.1665 tons of silica reacts with 0.222 tons of sodium hydroxide to produce 0.338 tons of sodium silicate). Through stacking, neutralizing, and static reaction, sodium hydroxide dissolves silica to form sodium silicate under the catalytic action of residual carbon. The completed reaction mixture is washed and dissolved with clear water to dissolve out the sodium silicate solution, and then the sodium silicate solution is filtered out through a plate and frame filter press to be separated from the filter cake. The filter cake is slag 3. The remaining solid residual carbon in it is washed with clear water to wash out the remaining residual salt, and then dried and activated to make activated carbon or added to the comprehensive utilization process of fly ash and coal gangue for repeated utilization.
[0184] The sodium silicate clear liquid filtered out by pressure filtration completes acid - method ion exchange by absorbing carbon dioxide in the process tail gas to displace silicic acid and sodium carbonate (i.e., Na2SiO3 + CO2 + H2O = H2SiO3 + Na2CO3, 0.338 tons of sodium silicate absorbs 0.1213 tons of carbon dioxide to produce 0.215 tons of silicic acid and 0.2924 tons of sodium carbonate). Because of the different conditions for the formation of silicic acid, it exists in the form of orthosilicic acid. The surface network structure of orthosilicic acid crystals is loose, in a small - molecule form, and the structure is unstable. It is soluble in water and acid solutions. In order to optimize and improve its material properties, in this embodiment, it is transformed into metasilicic acid in a boiling environment above 102°C through hydrothermal synthesis method, and then dehydrated and dried to make silica products.
[0185] As can be seen from the above embodiments, the present invention provides a process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas. To treat 1 ton of gasification slag, alumina is extracted by polybasic acids (H2SO4: 10%, HNO3: 10%, HCl: 10%): 0.0396 tons of H2SO4, 0.05 tons of HNO3, and 0.2384 tons of HCl are consumed; 0.0459 tons of Al2(SO4)3, 0.0564 tons of Al(NO3)3, and 0.2826 tons of AlCl3 are generated; for extracting iron oxide: 0.0082 tons of H2SO4, 0.0106 tons of HNO3, and 0.0488 tons of HCl are consumed, and 0.0112 tons of Fe2(SO4)3, 0.0136 tons of Fe(NO3)3, and 0.0728 tons of FeCl3 are generated. The aluminates and ferrites are replaced by ammonia to generate aluminum hydroxide and iron hydroxide. For replacing 0.0459 tons of aluminum sulfate, 0.028 tons of ammonia are consumed, and 0.0209 tons of aluminum hydroxide are produced; for replacing 0.0564 tons of aluminum nitrate, 0.0278 tons of ammonia are consumed, and 0.0206 tons of aluminum hydroxide are produced; for replacing 0.2826 tons of aluminum chloride, 0.2226 tons of ammonia are consumed, and 0.1654 tons of aluminum hydroxide are produced. For replacing 0.01123 tons of iron sulfate, 0.00309 tons of ammonia are consumed, and 0.00315 tons of iron hydroxide are produced; for replacing 0.01384 tons of iron nitrate, 0.059 tons of ammonia are consumed, and 0.0055 tons of iron hydroxide are produced; for replacing 0.07312 tons of iron chloride, 0.0464 tons of ammonia are consumed, and 0.048 tons of iron hydroxide are generated; after the aluminates and ferrites are replaced by ammonia, a total of 0.3868 tons of ammonia are consumed, and 0.2636 tons of aluminum hydroxide are produced; the aluminum hydroxide is dried and calcined to generate 0.140 tons of alumina; or it is converted into aluminum chloride by the hydrochloric acid conversion method, converting 0.2636 tons of aluminum hydroxide, consuming 1.12 tons of hydrochloric acid, and converting into 1.3733 tons of aluminum chloride; the remaining slag after acid leaching for aluminum and iron extraction is melted by the strong base melting method, dissolving 0.183 tons of silicon dioxide, consuming 0.246 tons of sodium hydroxide, and generating 0.374 tons of sodium silicate; the sodium silicate is subjected to ion exchange by absorbing carbon dioxide, treating 0.374 tons of sodium silicate, absorbing 0.134 tons of carbon dioxide, displacing 0.239 tons of silicic acid, and 0.3249 tons of sodium carbonate; the sodium carbonate is treated by the causticization reaction, consuming 0.2269 tons of calcium hydroxide, generating 0.3065 tons of calcium carbonate, and displacing 0.2452 tons of sodium hydroxide; the residual carbon in the gasification slag is transformed into 20 tons of activated carbon through reciprocating acid impregnation and alkali impregnation, and its surface area is greater than 900m 2 / g. The base amount of gasification slag processed by the process of the present invention is 1 ton, with a total consumption of 0.4786 tons of sulfuric acid, 0.6073 tons of nitric acid, and 0.3606 tons of hydrochloric acid, generating 0.2636 tons of aluminum hydroxide; consuming 0.246 tons of sodium hydroxide, 0.2269 tons of calcium hydroxide, generating 0.215 tons of silicic acid, and producing 0.165 tons of silicon dioxide after drying and calcination; generating 0.3065 tons of calcium carbonate, generating 0.2452 tons of sodium hydroxide; and transforming into 0.2 tons of activated carbon.
[0186] The present invention takes the comprehensive treatment of coal chemical waste gasification slag as the basis for extracting high-value minerals from fly ash and coal gangue. By treating the gasification slag, the residual carbon residue therein is transformed into activated carbon, which is continuously used in the treatment of other solid wastes and becomes a catalyst for the subsequent treatment process. Under the combined action of the aqua regia effect of polybasic acid and the electrochemical activation energy of the catalyst, the chemical reactions of aluminum and silicon extraction in each step are easily achieved; through the aqua regia effect generated by polybasic acid in dissolving metal oxides, the oxidation performance of the oxidant is improved. Under the electrochemical action of the catalyst and the promoter, the reaction activity of the oxidant is enhanced, the oxidation performance of the oxidant is improved, and the chemical structure of the reactant is easily destroyed, so that the chemical transformation that is difficult to achieve by conventional reactions is easily completed; the conventional dynamic chemical reaction mode is changed to a static stacking neutralization reaction mode, so that the super strong acid reacts with aluminum oxide and iron oxide in the ash slag to be transformed into soluble aluminates and ferrites during the static reaction; the pH value of the aluminates and ferrites is adjusted by the ammonia replacement method, and the iron and aluminum hydroxides are separated step by step while obtaining the hydroxides; the hydrochloric acid adjustment method is used to add hydrochloric acid to the aluminate and ferrite solutions to produce the common ion effect, promoting the rapid crystallization of aluminum chloride and separating it from the sulfuric acid and nitric acid residual liquids; the strong alkali melting method is used to carry out a static reaction between the separated silicon dioxide after aluminum extraction and the concentrated sodium hydroxide solution in a stacking container, so that the silicon dioxide in the sodium hydroxide molten slag material generates sodium silicate; the carbonation method is used to displace silicic acid and sodium carbonate solution from the sodium silicate clear liquid by absorbing carbon dioxide in the process tail gas; the causticization method is used to carry out a causticization reaction between the sodium carbonate solution and calcium hydroxide to produce the circulating solvent sodium hydroxide for melting silicon dioxide. The continuously improved residual carbon after the treatment of the gasification slag by the continuous acid dissolution and alkali dissolution process is repeatedly impregnated in the aluminum and silicon extraction of fly ash and coal gangue fine powder, so that the specific surface area of the residual carbon is continuously expanded and the activation energy is continuously enhanced, and finally it is transformed into activated carbon with excellent performance and properties; by modulating the use of oxidants such as H2O2, HClO4, HClO3, HClO2, and HClO, the chemical reaction of stacking neutralization obtains super strong divergence force and becomes a promoter that can boost chemical reactions. The invention comprehensively uses processes such as strong acid combination, stacking neutralization reaction, residual carbon impregnation transformation, ammonia replacement adjustment, common ion effect accelerated crystallization, and strong alkali melting, combines the characteristics and advantages of various processes and technologies, realizes the collaborative treatment and resource utilization of industrial waste gasification slag, fly ash, coal gangue and carbon dioxide in the waste gas while developing a huge amount of secondary resources, and enables the three solid wastes and carbon dioxide in the tail gas to produce a synergistic effect in the comprehensive treatment, excavates the catalyst activated carbon that helps the solid waste treatment, makes it an important intermediate in chemical reactions while greatly increasing its own value, and finally realizes the purpose of comprehensive treatment and resource utilization of various solid wastes through the combined use of various processes.
[0187] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas, characterized in that, It includes the following steps: Step 1): Mix the gasification slag, hydrochloric acid solution, sulfuric acid solution and nitric acid solution in sequence to obtain Slurry 1, then mix the catalytic promoter with Slurry 1 to obtain Slurry 2. After that, enhance the chemical reaction under the catalytic action of the surface activity of the residual carbon and the assistance of the promoter, and successively carry out stacking neutralization, washing and dissolution, and pressure filtration separation to obtain Slag Material 1 and Mixed Liquid 1; The Mixed Liquid 1 is a mixed solution containing aluminate and ferrate; Step 2): Adopt the ammonia replacement method to first replace ferric hydroxide and heavy metal hydroxides in the Mixed Liquid 1, raise the pH value to replace aluminum hydroxide precipitate and ammonium polyacid solution, heat-treat the aluminum hydroxide precipitate to make alumina finished product, or make aluminum chloride finished product by neutralization reaction with hydrochloric acid; Step 3): Subject the obtained ammonium polyacid solution to pyrolysis to obtain ammonia gas and polyacid residual liquid. The ammonia gas is recycled to the ammonia replacement method in Step 2), and the polyacid residual liquid is recycled to the preparation of Slurry 1; Step 4): Carry out the first alkali dissolution on the obtained Slag Material 1, and then successively carry out water dissolution and pressure filtration separation to obtain Mixed Liquid 2 and Slag Material 2; The Mixed Liquid 2 is a mixed liquid containing sodium silicate and sodium tetrahydroxyaluminate; Step 5): Carry out the second alkali dissolution on the obtained Slag Material 2, successively carry out water dissolution and pressure filtration separation to obtain Mixed Liquid 3 and Slag Material 3. Slag Material 3 is made into activated carbon through drying and activation, and then mixed with fly ash and / or coal gangue fine powder as a catalyst and recycled to Step 1); The Mixed Liquid 3 is a mixed liquid containing sodium silicate; Step 6): The Mixed Liquid 2 reacts by absorbing carbon dioxide produced in the process tail gas, and is filtered to obtain Solid 1 and sodium carbonate solution; Solid 1 is a mixture of silicic acid and aluminum hydroxide; Step 7): The Mixed Liquid 3 reacts by absorbing carbon dioxide produced in the process tail gas, and is filtered to obtain silicic acid and sodium carbonate solution; Step 8): Combine the sodium carbonate solutions obtained in Step 6) and Step 7), add calcium hydroxide for causticization reaction to obtain sodium hydroxide solution and calcium carbonate. The sodium hydroxide solution can be recycled, and the calcium carbonate is made into a finished product through drying; Step 9): Subject the silicic acid obtained in Step 7) to hydrothermal synthesis and then dry it to make a silica product. Mix the mixture of silicic acid and aluminum hydroxide obtained in Step 6) with the heavy metal hydroxides obtained in Step 2) to prepare high-aluminum molecular sieve.
2. The process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1, wherein In Step 1), the main components of the gasification slag include alumina and iron oxide; According to the component contents of alumina and iron oxide in the gasification slag, the dosage of the acid is prepared by calculating the mass percentage of various acids consumed in converting alumina and iron oxide according to the chemical reaction formula; The mass concentration of the hydrochloric acid solution is 35 - 37%, the mass concentration of the sulfuric acid solution is 50 - 98%, the mass concentration of the nitric acid solution is 50 - 98%, and the ratio of the hydrochloric acid solution, sulfuric acid solution and nitric acid solution is 5 - 15%: 5 - 15%: 70 - 90%; The catalytic action of the surface activity of the residual carbon refers to that the abundant active sites on the surface of the residual carbon have the ability to accept electrons and donate electrons, and can generate electrochemical reactions.
3. A process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1, characterized in that, In step 1), the catalytic promoter includes hydrogen peroxide solution and / or chloric acid solution. The volume concentration of the hydrogen peroxide solution is 27.5 - 40%, the concentration of the chloric acid solution is 25 - 30%, and the chloric acid in the chloric acid solution includes one or more of HClO4, HClO3, HClO2, and HClO; The total amount of the hydrogen peroxide solution and the chloric acid solution accounts for 5 - 10% of the sum of the masses of the hydrochloric acid solution, sulfuric acid solution, and nitric acid solution.
4. A process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1 or 2, characterized in that, In step 1), the temperature of the heap retting and neutralization is 50 - 80 °C, and the time of the heap retting and neutralization is 8 - 12 h; The washing and dissolving is washing and dissolving with clear water, and the water-to-material ratio is 3 - 5:
1.
5. A process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1 or 3, characterized in that, In step 2), the ammonia replacement method includes adding ammonia water or introducing ammonia gas.
6. The industrial solid waste and CO2 collaborative treatment and resource utilization process according to claim 5, characterized in that, In step 2), the aluminum hydroxide precipitate is heat-treated to produce alumina products. When the temperature is 140 - 150 °C, γ-alumina is obtained; When the heat treatment temperature is 900 °C - 1200 °C, α-alumina is obtained; In the hydrochloric acid neutralization reaction, the concentration of the hydrochloric acid solution is ≥25 wt%; In the hydrochloric acid neutralization reaction, aluminum chloride crystals are rapidly crystallized out from the aluminum chloride solution through the common ion effect. The crystals are aluminum chloride hexahydrate, and the mass concentration of the added hydrochloric acid is greater than 30%.
7. A process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1, characterized in that, In step 4), the reagent used for the first alkali dissolution is sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is 20 - 42%.
8. A process for the collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1 or 7, characterized in that In step 5), the reagent used for the second alkali dissolution is sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is 30 - 42%.
9. The process for collaborative treatment and resource utilization of industrial solid waste and CO2 in tail gas according to claim 1, characterized in that, In step 5), the volume ratio of the fly ash and / or coal gangue fine powder to the activated carbon is 1:0.2 - 0.5.
Citation Information
Patent Citations
Method for preparing soluble silicate with high modulus by gasified slag
CN108584971A
Industrial solid waste cooperative treatment system and process
CN115504478A
Gasification slag high-value resource utilization method
CN116140341A
Large-cycle process for coal ash alkali-acid alternate aluminum extraction and flue gas decarburization synergistic effect
CN117985727A
Method for producing aluminium oxide by processing fly ash with ammonia process
WO2013040862A1
Cited By
Carbonate mineralization CO2 storage method based on vanadium-containing shale tailings
CN120828043A